2018
DOI: 10.1053/j.jfas.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Achilles Tendon Augmented Repair Using Human Acellular Dermal Matrix: A Case Series

Abstract: Achilles tendon ruptures are common in the general population, especially among members of the older demographic occasionally active in sports. Operative treatments provide a lower incidence of rerupture than do nonoperative treatments, although surgical complications remain a concern. The use of a human acellular dermal matrix to augment Achilles tendon repair might reduce the incidence of complications. In the present case series, we describe the outcomes of 9 patients who underwent Achilles tendon repair wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…There were 21 patients with good clinical and patient-reported short-term (24 weeks) results who returned to full activities in 12 weeks. In another case series of nine patients who underwent Achilles tendon repair with accellular dermal matrix augmentation, no re-ruptures or complications were reported in any of the patients with a minimum follow-up period of 2 years [35].…”
Section: Biological Scaffoldsmentioning
confidence: 91%
“…There were 21 patients with good clinical and patient-reported short-term (24 weeks) results who returned to full activities in 12 weeks. In another case series of nine patients who underwent Achilles tendon repair with accellular dermal matrix augmentation, no re-ruptures or complications were reported in any of the patients with a minimum follow-up period of 2 years [35].…”
Section: Biological Scaffoldsmentioning
confidence: 91%
“…We expect the strength of the ADM to be sufficient to prevent bowstringing, given documented durability in hernia repair, superior capsular reconstruction for irreparable rotator cuff tears, and Achilles tendon repair augmentation. 15,16 We expect that ADM provides an antiadhesive surface and low gliding resistance similar to that of the native pulley system. Even in hostile environments, such as prior radiation and chronic inflammation, ADM can incorporate and take on the lubricating properties of surrounding tissues.…”
Section: Expected Outcomesmentioning
confidence: 99%
“…[10,11] It is reported that the acellular dermal matrix (ADM), commonly used as a replacement for skin grafts and a supplement for tissue defects, [12] has been applied for tendon augmentation in Achilles tendon repair and as tendon scaffold in tendon gap repair. [13][14][15] However, to our knowledge, the effects of using an ADM as the mechanical anti-adhesive barrier when repairing flexer tendon injuries have not been documented yet. In this study, we present the long-term outcomes of a randomized prospective study in which ADM was used to prevent postoperative adhesions after tendon injury.…”
Section: Introductionmentioning
confidence: 99%